MODERN METHODS OF POLYETHYLENE WASTE RECYCLING AND THEIR ENVIRONMENTAL EFFICIENCY - A.E.Mendygaliyeva *,N.S.Yerzhanova,A.Bayode,R.N.Kubasheva,B.М.Kussainova (Вестник ЗКУ, 2026)
The article examines modern methods of polyethylene waste recycling and provides a comprehensive assessment of their environmental efficiency in the context of sustainable development and reducing anthropogenic pressure on the environment. The relevance of the study is обусловлена the growing volume of polymer waste, the low level of its utilization, and the negative impact of polyethylene on ecosystems.The main approaches to polyethylene recycling are analyzed, including mechanical recycling, chemical methods (pyrolysis, gasification, depolymerization), as well as innovative «green» technologies aimed at reducing harmful emissions and energy consumption. It is shown that mechanical recycling is the most economically and environmentally justified method when an effective system of separate collection and sorting of waste is in place, as it preserves the material value of polymers and reduces the demand for virgin raw materials. At the same time, chemical recycling methods have the potential to process mixed and contaminated polyethylene waste, expanding opportunities for the reuse of polymer feedstock and the production of alternative fuels and chemical products.The advantages and limitations of each method are identified, including energy consumption levels, greenhouse gas emissions, technological complexity, and the quality of the recycled product. It is concluded that the integrated and differentiated application of various polyethylene waste recycling methods is a key condition for minimizing environmental risks and transitioning to a circular economy model.